Pengaruh Pemberantasan Illegal Fishing Di Perairan Indonesia Terhadap Hubungan Bilateral Indonesia Dengan Negara Lain - Ginting, Erina Bibina Br; Indra, Mexsasai; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
At first, the free sea voyage is open to everyone as well as the arrests of fish, but in the centuriesfifteenth and sixteenth periods where there is the great maritime discoveries by European sailors.Indonesia is the world's largest maritime countries that have vast seascape with thousands oflarge and small islands from Sabang to Merauke. Indonesia with a territory composed of 17,000islands, islands with a coastline of 81,900 km, and the area of water reaches 5.8 million km2have a great vulnerability in relation to the territory. Unfortunately, the vast potential of theoceans has not been able to be maintained to the maximum, while the activity of exploitingIndonesia's marine area for the purposes of exploration and exploitation of the economicpotential of the sea and marine transportation services is increasing, so the greater the potentialfor offense.Illegal fishing activities are most frequent in Indonesia is a fisheries management area of illegalfishing by foreign fishing boats hereinafter abbreviated as (KIA), which comes from severalneighboring countries. Formal legally illegal fishing by foreign vessels in the waters of Indonesiacan be categorized as an extraordinary crime. The main violations of sovereignty. The entry offoreign vessels illegally fishing in Indonesian territorial sea can be categorized endanger thepeace, good order or national security. The purpose of this thesis are: First, the process of lawenforcement at sea Indonesia against foreign fishing vessels that have violated the law, Secondly,Constraints and Indonesia's efforts related to law enforcement at sea Indonesia, Third, lawenforcement Effect Indonesia to bilateral relations. This type of research can be classified intotypes of normative, namely the study of the principles contained in international and nationallaw.This study uses primary data, secondary data and data tertiary data collection techniques inresearch with the literature study. From the research, there are three main things that can beinferred. First, the government is more likely to burn and sink the ship rather than confiscated forstate assets, this action is considered able to provide a deterrent effect for offenders IllegalFishing. Second, the constraints faced by the government are limited facilities and infrastructureso it can not oversee the territorial waters of the maximum, there is also some debate amongrelevant authorized agencies authority of each institution are often collide. Third, the foreignfishing vessel sinking a few countries that protested, and therefore it is important for thegovernment to immediately make the rules of national law governing bail bond, so as not toburden the future position of Indonesia in the international scope.Keywords: Eradicate -Illegal Fishing- Relationship- Bilateral